AKIBAT HUKUM PEMISAHAN KEKAYAAN NEGARA MELALUI PENYERTAAN MODAL (Faculty of Law, University of Dr. Soetomo, 2018)
The present state finances can not be seen as only the state's role as the authority, the roles / actions outlined in the State Budget. Differences in the understanding of state finances is also due to differences in the definition of state losses. Not only related to the definition of loss to the state, problems related to the wealth of a country that has invested in state-owned through equity participation led to various problems, among others related to the status of the State Treasury were separated. Besides the differences in the definition of the State Treasury and Financial Limited, causing some company directors who have capital from countries not hesitate in taking business decisions because they must be confronted with the threat of the risk of financial loss to the country and the threat of corruption. If the loss is equal to loss of state-owned it conflicts with limited liability.